The Analysis of Rainfall and Surface Runoff in Nam Lik Watershed, Vientiane Province: The Analysis of Rainfall and Surface Runoff in Nam Lik Watershed, Vientiane Province - Phimmathat, Khen; Keokhamphui, Khaykeo; Kinglattana, Latsamee; Xaisongkham, Anusone; Dalasang, Somkhit (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to 1) analyze daily rainfall by creating 24-hour rainfall lines, and 2) estimate surface runoff in the Nam Lik Watershed of ​​Vientiane Province. The study used 4 rainfall measurement stations: Kasi, Vang Vieng, Hin Heup, and Phon Hong, with 15 years of data to analyze the maximum rainfall in the annual cycle and create a 24-hour rainfall distribution layer. In addition, this data was used to estimate the daily surface runoff in the Nam Lik Watershed. Using three methods to calculate Log Person Type III, Gumbel method with calculation and Gumbel method with graph, and to evaluate the appropriate parameter values ​​for estimating surface runoff using the SWAT Model. The results of found that the distribution of daily rainfall intensity is in Vang Vieng, with an average daily rainfall between 11.57-12.87 mm/day, and the average daily rainfall distribution at Kasi and Hin Heup stations is between 6.29-6.99 mm/day. From the analysis of the maximum rainfall that can occur in the duplication trend year periods. of the rainfall measuring stations near the Nam Lik Watershed, 3 calculation theories. From the calculation results, it is seen that the maximum rainfall occurs in the duplication trend year periods. The Vang Vieng rainfall measuring station is not much different compared to the three stations near the Nam Lik Watershed, and the rainfall intensity increases with the duplication trend in yearly periods. The runoff volume estimation at Nam Lik Watershed show that the values ​​of R2, NSE that formulated from chaning an actual value of water flow volume and the model measured at Vangvieng and Hin Heup rainfall station found that R2 = 0.74, NSE = 0.72, R2 = 0.57, NSE = 0.52, the highest daily runoff volume is 945 m3/s at Vanvieng station, the lowest dialy flow volume is 7.25 m3/s, and the average dialy flow volume is 85.98 m3/s. The highest daily runoff volume at Hin Heup station is 2,593 m3/s, the lowest daily flow volume is 3.75 m3/s, and the average daily flow volume is 187.53 m3/s. The highest dialy runoff volume at Num Lik Outlet is 5,024 m3/s, the lowest dialy flow volume is 2.58 m3/s, and the average dialy flow volume is 313.21 m3/s.